As time goes by: Evolutive interplay between endogenous retrolements and the KRAB’n’KAP system - Imbeault, Michael (Dev Cell, 2014)
Close to 50% of the human genome is derived from endogenous retroelements, which are both formidable evolutionary forces and threats to its integrity. Accordingly, these genetic invaders are subjected to transcriptional repression from the very first days of embryogenesis. Reporting in Nature, Jacobs et al. help us understand the sequence-specificity of this process, by identifying two members of the KRAB-containing zinc finger protein family responsible for silencing particular subsets of L1 and SVA in humans (Jacobs et al., 2014). A ray of light is shed on evolutionary forces that shape the interplay between mobile elements and their hosts.